Alcohol Use is Not Directly Related to the Perceived Control of Depressive Symptoms in Patients with Depressive Symptoms - Skule, Cecilie (Frontiers Media S.A., 2014)
Treatment-seeking patients (N = 233) were recruited as they started a course of relapse prevention and coping with depression. The mean Beck depression inventory (BDI-II) score was 26 points, indicating a moderate degree of depression. The sample was recruited from different outpatient clinics and screened for alcohol-related problems with the alcohol use disorders identification test (AUDIT). Almost half of the total sample had a score on AUDIT >8 indicating an alcohol problem. The participants in this study did not undergo a clinical interview to check out if their symptoms, as assessed with BDI-II and AUDIT, were part of a formal diagnosis in accordance with the criteria in ICD 10 or DSM IV. A specific instrument, perceived uncontrollability of depression (UNCONTROL), was used to measure the persons’ perceived control of depressive symptoms; a set of statements about coping with depressive symptoms where high scores indicate lack of coping with the symptoms. Alcohol problems were not found to be significantly associated with the perceived control of ongoing depressive symptoms and did not moderate the relationship between depressive symptoms and the perceived control of depressive symptoms. The results question the assumption that alcohol use is related to coping with depressive symptoms in patients with alcohol abuse and depressive symptoms.